An in vitro study on the antimicrobial property of Malaysian honey and propolis extracts against microorganism implicated in denture stomatitis - Yusoff, Nik Yusliyana Nik (2018)
Denture stomatitis presents as a chronic disease commonly occurs under maxillary prosthesis. Despite the existence of a great number of antibacterial and antifungal agents, treatment failure is observed frequently. An alternative solution is to find material that has antibacterial and antifungal properties of equivalent nature to the action of miconazole and chlorhexidine. It must be well tolerated by the body, causing no side effects or interference with drug metabolism. Honey and propolis seem to fit all the criteria mentioned above. Honey and propolis have anti-inflammatory, antimicrobial, antioxidant and anticancer properties. The aim of the current study was to investigate the physical andantimicrobial properties of honey and propolis extracts of Apis dorsata, Apis mellifera and Trigona spp. against common microorganisms implicated in denture stomatitis. The physical properties of honey were examined based on colour, acidity and moisture content. The efficacy of honey and propolis extracts towards microorganisms was evaluated by using agar well diffusion assay. The effective concentrations of the honey and propolis extracts were determined by Minimum Inhibitory Concentration (MIC). In physical test, the data are presented as mean and standard deviation of each of the attributes. For agar well diffusion assay, three-way ANOVA followed by post-hoc comparison was used for statistical analysis (p < 0.05). For determination of minimum inhibitory concentration, the reading from ELISA reader and visual observation werereported on the concentration of honey and propolis extracts. The results showed that Malaysian honey exhibited better acidity and highest moisture content than the benchmark, Apis mellifera honey. For result of agar well diffusion assay, Trigona spp. honey exhibited favourable antimicrobial activity against several microorganisms with large inhibition zones against Actinomyces sp and Candida tropicalis at 25.79±0.32 mm and 12.29±0.23 mm, respectively. For MIC value of honey, Trigona spp showed lowest MIC value against Staphylococcus aureus and Actinomyces spp. at 62.5mg/ml while against all Candida spp. at 250mg/ml. The propolis extract from Trigona spp.exhibited better antibacterial activity compared to propolis extract from Apis mellifera against S. aureus and Streptococcus mitis at 13.58±0.90 mm and 14.05±0.13 mm, respectively with no antifungal activity against Candida spp. For MIC value of propolis extracts, Trigona spp. showed lowest MIC against S. aureus and S. mitis at 62.5mg/ml while 500mg/ml against all Candida spp.The MBC value was higher than MIC value for honey and propolis. Hence, it can be concluded that Malaysian honey and propolis extract mainly Trigona spp. exhibited better antimicrobial activity than Apis mellifera against microorganisms implicated in denture stomatitisand have potential usage in the treatment of common oral diseases.